Establishing an occupational health & safety management system based on ISO 45001 - Sadiq, Naeem (IT Governance Publishing, 2019)
This book provides a comprehensive explanation of the detailed requirements of ISO 45001. The author draws out key parts of the Standard, which can often be confusing for non-experts or newcomers to ISO standards, and explains what they mean and how to comply.